Local crowding out in China - Yi Huang; Marco Pagano; Ugo Panizza (Goethe University Frankfurt, Center for Financial Studies (CFS), 2019)
In China, between 2006 and 2013, local public debt crowded out the investment of private firms by tightening their funding constraints, while leaving state-owned firms' investment unaffected. We establish this result using a purpose-built dataset for Chinese local public debt. Private firms invest less in cities with more public debt, the reduction in investment being larger for firms located farther from banks in other cities or more dependent on external funding. Moreover, in cities where public debt is high, private firms' investment is more sensitive to internal cash flow, also when cash-flow sensitivity is estimated jointly with the probability of being credit-constrained.
urn:nbn:de:hebis:30:3-515873
Keywords: E22; H63; H74; L60; O16; 330; investment; local public debt; crowding out; credit constraints; China